Pengaruh Diskon, Electronic Word of Mouth (E-WOM), dan Service Quality terhadap Keputusan Pembelian Game di Platform Steam : Survei pada Komunitas Steam User Indonesia - Hanura Kevin Chrysandro; Mutya Paramita Pratita (Jurnal Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the influence of service quality, discounts, and electronic word of mouth (E-WOM) on users’ purchasing decisions in playing and buying games on the Steam platform. The background of this research is based on the growing competition in the digital gaming industry, which requires service providers to understand the key factors that shape consumer behavior. Data were collected using purposive sampling by distributing questionnaires to 100 active members of the Steam User Indonesia Community who have direct experience with the platform. The data were analyzed through several statistical tests, including the coefficient of determination, instrument testing, classical assumption testing, multiple linear regression, t-test, and F-test, in order to test the proposed hypotheses. The results reveal that discounts and E-WOM significantly influence users’ purchasing decisions, while service quality does not have a significant effect. The adjusted R² value of 0.461 indicates that the three independent variables in this study explain 46.1% of the variance in purchasing decisions, with the remaining percentage influenced by other factors outside the research model. These findings suggest that effective discount strategies and positive user-generated reviews or recommendations play a crucial role in encouraging purchasing decisions on the Steam platform.